2015
DOI: 10.1155/2015/346036
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of TAGE Method Using Seikkala Derivatives Applied to Two-Point Fuzzy Boundary Value Problems

Abstract: Iterative methods particularly the Two-Parameter Alternating Group Explicit (TAGE) methods are used to solve system of linear equations generated from the discretization of two-point fuzzy boundary value problems (FBVPs). The formulation and implementation of the TAGE method are also presented. Then numerical experiments are carried out onto two example problems to verify the effectiveness of the method. The results show that TAGE method is superior compared to GS method in the aspect of number of iterations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The generated linear systems are then resolved by the TAGE method iteratively. Previous studies associated to the TAGE iterative technique and its modification [11][12][13] have demonstrated that this approach was used extensively to unravel the problems in non-fuzzy cases. This article widens the use of the TAGE iterative approach to solve fuzzy issues because of the efficiency of the methods.…”
Section: Introductionmentioning
confidence: 99%
“…The generated linear systems are then resolved by the TAGE method iteratively. Previous studies associated to the TAGE iterative technique and its modification [11][12][13] have demonstrated that this approach was used extensively to unravel the problems in non-fuzzy cases. This article widens the use of the TAGE iterative approach to solve fuzzy issues because of the efficiency of the methods.…”
Section: Introductionmentioning
confidence: 99%